Amnesia Associated with Bilateral Hippocampal and Bilateral Basal Ganglia Lesions in Anoxia with Stimulant Use - Haut, Marc W.; Hogg, Jeffery P.; Marshalek, Patrick J.; Suter, Blair C.; Miller, Liv E. (Frontiers in Neurology, 2017)
We report a case of a 55-year-old man with ischemic lesions of the bilateral hippocampus and bilateral basal ganglia following a myocardial infarction during an episode of multiple drug use with subsequent anoxia requiring resuscitation. He presented for a neuropsychological evaluation with an anterograde amnesia for both explicit and procedural memory. There are two main points to this case, the unique aspects of the bilateral multifocal lesions and the functional, cognitive impact of these lesions. We hypothesize that his rare focal bilateral lesions of both the hippocampus and basal ganglia are a result of anoxia acting in synergy with his stimulant drug use (cocaine and/or 3,4-methylenedioxy-methamphetamine). Second, his unique lesions produced an explicit and implicit/procedural anterograde amnesia.